The Implementation Mind Mapping Method to Improve Reading Comprehension of the Eleventh Grade Students of SMA Negeri 5 Palu - Labaso, Arini; Marhum, Mochtar; Dewi, Anjar Kusuma (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study investigates the implementation of the Mind Mapping method to improve reading comprehension among eleventh-grade students at SMAN 5 Palu. The purpose of this study is to examine the effect of mind mapping on students’ reading comprehension. A quantitative experimental design was employed, with the sample divided into two groups: an experimental group of 35 students taught using the mind mapping method and a control group of 31 students taught through conventional instruction. Pre-tests and post-tests were administered, and the results showed that students taught using mind mapping had better reading comprehension. The data analysis indicated that the mean pre-test score of the experimental group was 46 and the control group 51, which increased after the intervention to 75 for the experimental group and 61 for the control group. An independent sample t-test was conducted, resulting in a t-count of 7.261 compared to a t-table value of 1.997, with 64 degrees of freedom and a significance level of 0.05. Since the t-count exceeds the t-table, the hypothesis is accepted. These findings demonstrate that mind mapping is effective in enhancing reading comprehension, and English teachers are recommended to apply this technique as an easy and effective strategy to help students understand texts